Comparison of Manual versus Automated Data Collection Method for an Evidence-Based Nursing Practice Study - Byrne, M.D.; Jordan, T.R.; Welle, T. (Applied Clinical Informatics, 2013)
Objective: The objective of this study was to investigate and improve the use of automated data collection procedures for nursing research and quality assurance.Methods: A descriptive, correlational study analyzed 44 orthopedic surgical patients who were part of an evidence-based practice (EBP) project examining post-operative oxygen therapy at a Midwestern hospital. The automation work attempted to replicate a manually-collected data set from the EBP project.Results: Automation was successful in replicating data collection for study data elements that were available in the clinical data repository. The automation procedures identified 32 “false negative” patients who met the inclusion criteria described in the EBP project but were not selected during the manual data collection. Automating data collection for certain data elements, such as oxygen saturation, proved challenging because of workflow and practice variations and the reliance on disparate sources for data abstraction. Automation also revealed instances of human error including computational and transcription errors as well as incomplete selection of eligible patients.Conclusion: Automated data collection for analysis of nursing-specific phenomenon is potentially superior to manual data collection methods. Creation of automated reports and analysis may require initial up-front investment with collaboration between clinicians, researchers and information technology specialists who can manage the ambiguities and challenges of research and quality assurance work in healthcare.Citation: Byrne MD, Jordan TR, Welle T. Comparison of Manual versus Automated Data Collection Method for an Evidence-Based Nursing Practice Study. Appl Clin Inf 2013; 4: 61–74http://dx.doi.org/10.4338/ACI-2012-09-RA-0037
Keywords: Automation; comparative study; data collection; evidence-based nursing; nursing methodology research